Neo-existentialism how to conceive of the human mind after naturalism's failure - Gabriel, Markus 1980- (Polity Press, 2018)
"In this highly original book, Markus Gabriel presents 'Neo-Existentialism', an anti-naturalist view that holds that human mindedness consists in an open-ended proliferation of mentalistic vocabularies. Challenged by Charles Taylor, Andrea Kern and Jocelyn Benoist, Gabriel deftly refutes naturalism's metaphysical claim to epistemic exclusiveness"...
Includes bibliographical references and index
Keywords: Naturalism; Existentialism; Naturalismus -- Philosophie; Existenzphilosophie; Aufsatzsammlung